1989
DOI: 10.1002/ajmg.1320330426
|View full text |Cite
|
Sign up to set email alerts
|

Autosomal recessive form of whistling face syndrome in sibs

Abstract: Two sibs with the whistling face syndrome, born to unaffected parents, are presented. They had the full facial and limb manifestations typical of this disorder, for which there is evidence of autosomal dominant inheritance. The existence of an autosomal recessive form of this syndrome has been suspected previously on the basis of a limited number of observations. Our study substantiates genetic heterogeneity of this condition and suggests that the autosomal recessive form could be even less rare than is genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 12 publications
0
7
0
1
Order By: Relevance
“…Temtany and McKusick [9] observed that FSS affected two generations of three different families. However, there are also reports of the syndrome suggesting an autosomal recessive inheritance; in other words, of affected children born to parents who were clinically normal but possible carriers (heterozygotic) of the gene responsible for the syndrome [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Temtany and McKusick [9] observed that FSS affected two generations of three different families. However, there are also reports of the syndrome suggesting an autosomal recessive inheritance; in other words, of affected children born to parents who were clinically normal but possible carriers (heterozygotic) of the gene responsible for the syndrome [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Their definition of a distal arthrogryposis is “an inherited primary limb malformation disorder characterised by congenital contractures of two or more different body areas and without primary neurologic and/or muscle disease that affects limb function”. Indeed in most of the reported cases intelligence was described as normal; this includes all cases with autosomal dominant inheritance6 13 14 and some of the cases with autosomal recessive inheritance 12…”
mentioning
confidence: 99%
“…Genetically speaking, this syndrome is described as autosomal dominant, but relatively recently autosomal recessive cases have been reported with a very severe clinical profile [1][2][3][4]; some cases have been described as the result of a genetic mutation [5][6][7][8][9]. The genetic variability, still not completely understood regarding the exact site and extent of the genetic alterations, explains the extreme phenotypical variability and therefore makes differential diagnosis difficult.…”
Section: Discussionmentioning
confidence: 99%
“…One radiographic characteristic is the deformity of the skull that appears to be square with a prevalence of the neurocranium with respect to the facial cranium; the occipital fossa appears deep-set, the occipital foramen is verticalized and oriented backwards [5][6][7][8][9][10][11][12][13][14][15]. Intelligence is generally normal, although cases have been reported of mental delay combined with EEG anomalies and cerebella and cortical atrophy as seen on the CT scan.…”
Section: Bilateral Clubfoot (Generally Equinus-varus-supine)mentioning
confidence: 99%